Manajemen Mutu Integratif Lembaga Pendidikan Islam di MTsN 7 Tulungagung - Desi Dwi Anissa; M Rikza Chamami (Faculty of Education and Teacher Training of UINSI Samarinda, 2026)
Improving madrasah quality requires integrated governance because institutional growth, educational services, and student achievement do not automatically develop at the same pace. This study examined integrative quality management at MTsN 7 Tulungagung through four key dimensions: educational facilities and infrastructure, administrative services, the capacity of teachers and education personnel, and student development. A descriptive qualitative case-study design was employed. Data were collected in 2025 through field observations, semi-structured interviews, and analysis of institutional documents, and were analyzed using data condensation, data display, conclusion drawing, and source-and-technique triangulation. The findings showed that the madrasah had strong institutional capital, including increasing public demand, Adiwiyata practices, research-madrasah status, religious habituation, and achievements at national and international competitions. However, the growth from 516 students in 2012/2013 to 924 students in 2024/2025 was not fully matched by support capacity: nine classrooms required repair, science and language laboratories were unavailable, most computers required maintenance or replacement, administrative work remained partly fragmented, and research and competition programs required additional specialist support and sustainable financing. The study concluded that the quality of the madrasah was produced by the interaction of responsive services, committed personnel, religious-environmental culture, and student-development programs, but its sustainability depended on data-based planning, continuous professional development, integrated administration, and prioritized facility investment.